PENGARUH PEMBERIAN SOLID KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Samuel P Hutabarat; Tengku Nurhidayah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this research is to determine the effect of oil palm solid waste and to get the best dose to increase the growth of cocoa seedlings. This research was conducted in the Experimental Garden of the Faculty of Agriculture, University of Riau in July to October 2018. This study used completely randomized design (CRD) consisting of 7 treatments and 3 replications. The treatment consisted of a solid dose of palm oil 0 g.10 kg-1 medium, 25 g.10 kg-1 medium, 50 g.10 kg-1 medium, 75 g.10 kg-1 medium, 100 g.10 kg-1 medium, 125 g.10 kg-1 medium and 150 g.10 kg-1 medium. The parameters observed were seedling height, seedling stem diameter, number of seedling leaves, seedling leaf area, seedling root volume, shoot and root ratio and seedling dry weight. The data obtained were analyzed using variance analysis and continued with Duncan's Multiple Range Test (DMNRT) at 5 % level. The results showed that the application of solid oil palm did not significantly affect the parameters of seedling height, seedling stem diameter, number of seedling leaves, seedling leaf area and volume of seedling roots and had a significant effect on the dry weight parameters of seedlings and giving of 75 g of solid palm oil/10kg medium is better to increase the growth of cocoa seedlings aged 4 months. Keywords: Growth, cocoa seedlings and palm oil solid waste